2019
DOI: 10.1111/joim.12897
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free tumour DNA testing for early detection of cancer – a potential future tool

Abstract: In recent years, detection of cell‐free tumour DNA (ctDNA) or liquid biopsy has emerged as an attractive noninvasive methodology to detect cancer‐specific genetic aberrations in plasma, and numerous studies have reported on the feasibility of ctDNA in advanced cancer. In particular, ctDNA assays can capture a more ‘global’ portrait of tumour heterogeneity, monitor therapy response, and lead to early detection of resistance mutations. More recently, ctDNA analysis has also been proposed as a promising future to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 159 publications
(204 reference statements)
0
55
1
Order By: Relevance
“…Molecules of cfDNA are rapidly cleared from the circulation, with a half-life ranging from minutes to several hours. Healthy individuals have cfDNA levels of 1-10 ng/ml which can increase by intense exercise, trauma, infections and inflammatory conditions [83]. Due to the small size it is expected that cfDNA can also be analyzed in urine, but concentrations will be influenced by the glomerular filtration rate [84].…”
Section: Cell-free Dnamentioning
confidence: 99%
“…Molecules of cfDNA are rapidly cleared from the circulation, with a half-life ranging from minutes to several hours. Healthy individuals have cfDNA levels of 1-10 ng/ml which can increase by intense exercise, trauma, infections and inflammatory conditions [83]. Due to the small size it is expected that cfDNA can also be analyzed in urine, but concentrations will be influenced by the glomerular filtration rate [84].…”
Section: Cell-free Dnamentioning
confidence: 99%
“…Although cfDNA is common even in healthy people, patients with cancer have higher blood levels of cfDNA (Leon et al 1977;Stroun et al 1987;Schwarzenbach et al 2011). The average proportion of mutated DNA in plasma is very low, 0.4% in even advanced cancers (Barbany et al 2019). Analysis of ctDNA is known as liquid biopsy.…”
Section: Cell-free Tumor Dna (Ctdna)mentioning
confidence: 99%
“…Somatic alterations were identified in 85% of the patients overall, with a range of 51% to 93% represented across various tumor types (Zill et al 2018). The posited applications of ctDNA include identification of disease progression (i.e., ductal carcinoma in situ to invasive ductal breast cancer), cancer screening in high-risk populations (i.e., prostate cancer in men over 70), and distinguishing benign from malignant disease (Barbany et al 2019). In addition to single-gene variants, it is possible that large CNVs or chromosomal disorders may be identified (Barbany et al 2019).…”
Section: Cell-free Tumor Dna (Ctdna)mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, liquid biopsy to detect cfDNA or circulating tumor DNA (ctDNA) has emerged as an attractive non-invasive methodology to discern cancerspecific genomic aberrations in plasma. Numerous studies have reported the utility of ctDNA in advanced cancer [194][195][196][197]. In particular, ctDNA assays can capture a more global portrait of tumor heterogeneity than that provided by tissue DNA (which reflects the small piece of tissue that is biopsied rather than DNA shed from both primary and multiple metastatic sites [198]); therefore, ctDNA can be exploited to monitor tumor response and resistance.…”
Section: Confounding the Holy Grail-early Detection Of Cancer With Blmentioning
confidence: 99%